Pemberdayaan Ekonomi Keluarga Melalui Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) (Studi Kasus di Desa Sukorejo Kecamatan Saradan Kabupaten Madiun) - Sudarmiani, Waini Astuti (Universitas PGRI Madiun, 2019)
This study aims to determine the implementation of the UPPKS program, the role of UPPKS cadres, the supporting components of the UPPKS program and obstacles in family economic empowerment activities through the UPPKS program in Sukorejo Village, Saradan, Madiun. The type of research used is descriptive qualitative with a case study approach. Data sources used are primary data and secondary data. Data collection is done by observation, interviews and documentation. The validity of the data uses source triangulation. The results show, (1) The implementation of family economic empowerment through the UPPKS program in Sukorejo Village runs quite well in savings and loan activities. (2) The role of UPPKS cadres in Sukorejo Village is as facilitators in conveying what their members want to the UPPKS program organizers. (3) Supporting components in the implementation of UPPKS activities in Sukorejo Village are Village Village, Saradan PLKB, and BKKBN. (4) Obstacles in the process of family economic empowerment through the UPPKS program in Sukorejo Village, namely the existence of members who are less active in the activities of UPPKS groups and members who move domiciles, so that UPPKS members are reduced.